Pengaruh Sudu dan Kecepatan Angin Terhadap Koefisien Torsi dan Koefisien Daya Serta Efisiensi Turbin Angin Savonius Sumbu Vertikal - Chaidir chaidir; Niharman niharman; Een Tonadi (MAJALAH TEKNIK SIMES, 2021)
Abstract The present paper is concerned with experimental study of performance of a vertical axis savonius wind turbine. Savonius turbine blades are made of PVC pipe and a fan to drive the turbine. The test was carried out with a different number of blades, namely 2 blades, 3 blades and 4 blades at air velocity of 3.6 m/s, 4.4 m/s and 5.8 m/s. The results obtained the highest maximum power efficiency is in the 3 blade test, namely at air velocity of 3.6 m/s of 0.156, air velocity of 4.4 m/s of 0.313 and air velocity of 5.8 m/s of 0.182. The maximum torque coefficient for the three air velocity also obtained the highest value in the 3 blade test. At a air velocity of 3.6 m/s, a torque coefficient of 0.641 is obtained, a air velocity of 4.4 m / s is 1.027 and a air velocity of 5.8 m/s is 0.745. The maximum efficiency in the 3 blades test with air velocities of 3.6 m/s, 4.4 m/s, and 5.8 m/s is obtained respectively 15.6%, 31.3% and 18.2% efficiency. In conclusion, the 3 blades wind turbine has the highest efficiency compared to the 2 and 4 blades tests. Meanwhile, the highest efficiency was obtained at a air velocity of 4.4 m / s with 3 blades, namely 31.3%.